ANALYSIS OF THE EFFECT OF KETAPANG LEAF EXTRACT (Terminalia catappa) ON THE GROWTH AND PROFILE OF BACTERIA IN THE MAINTENANCE OF INDIAN BOTIA FISH LARVAE (Botia lohachata) - Laily Fitriani Mulyani; Asri, Yuliana (Journal of Fish Nutrition, 2025)
This study aimed to evaluate the potential of ketapang leaf extract (Terminalia catappa) as an agent to enhance the survival and growth of Botia india (Botia lohachata) larvae, as well as its effect on the bacterial profile in the rearing medium. The experiment was conducted using a Completely Randomized Design (CRD) with five different treatment doses of ketapang leaf extract, namely 0 g/L (control), 0.3 g/L, 0.6 g/L, 0.9 g/L, and 1.2 g/L, each replicated three times. The observed parameters included survival rate, growth (absolute weight and absolute length), and the total bacterial count in the rearing medium. The results showed that the administration of ketapang leaf extract had a significant effect (p<0.05) on the survival, absolute weight, and absolute length of Botia india larvae. The treatment with a dose of 0.3 g/L resulted in the highest survival rate, reaching 95%, with an average larval absolute weight of 0.132 g and an absolute length of 1.35 cm. Quantitative analysis of the bacterial count showed that the administration of ketapang leaf extract, especially at a dose of 0.3 g/L, effectively suppressed bacterial growth in the rearing medium compared to the control group. Conversely, higher doses of ketapang leaf extract (0.9 g/L and 1.2 g/L) showed a tendency towards decreased effectiveness. The conclusion of this study is that ketapang leaf extract can be utilized as a natural alternative to improve the survival, growth, and health of Botia india larvae, with an optimal dose of 0.3 g/L. The utilization of ketapang leaf extract in ornamental fish farming can reduce dependence on synthetic chemicals that have potentially harmful environmental effects.